Futsal as a strategy for the improvement of elementary abilities and for the development of the body image in children - Amanda A. Machado; Ingrid S. Bezerra; Katia Regina Ponciano; Roberta L. Rica; Eliane F. Gama; Aylton Figueira Junior; Roberto Gimenez; Danilo Sales Bocalini (Desafio Singular, 2018)
This current study aims to analyze the contribution of futsal practice in global praxis and body image in children in a specialized motor stage, evaluating the motor performance before and after an intervention in the following factors: hands and feet global praxis and body image. It was adopted the application method of 18 one-hour twice a week session, divided into three modules, I) displacement activities in different directions; II) coordination activities and reaction time and III) throwing and kicking activities. Twenty male participants, aged 8 to 12 years, with normal motor development were used. The survey was conducted at a private school. The results found were a significant improvement in the hits of the tennis balls with hands and make the number of hits in kicking the ball with his feet. Regarding the analysis of body image after the proposed intervention, the children has shown the body parts performance incorporated in drawings that were not previously present. It is concluded that there are positive contributions of the futsal practice in respect to the global praxis practice and body image in children in a specialized motor stage.